Evaluasi Kebijakan Bantuan Keuangan Partai Politik dan Implikasinya terhadap Pendidikan Politik Masyarakat di Provinsi Lampung - Gede Ari Pratama Putra; Budhi Waskito; Riswan Riswan (PERSPEKTIF, 2026)
The Political Party Financial Assistance (Banparpol) policy is designed to support political education and strengthen democratic quality; however, its implementation at the regional level remains substantively limited. This study evaluates the implementation of Banparpol in Lampung Province and examines its implications for the quality of regional democracy. A qualitative case study approach was employed, using in-depth interviews, document analysis, and literature review, and the analysis was conducted through William N. Dunn’s policy evaluation framework. The Indonesian Democracy Index (IDI) was used as an outcome indicator. The findings reveal that Banparpol implementation is predominantly administrative, with political education activities being incidental and focused on internal party interests. Budget distribution based on electoral votes does not correspond to the quality of policy outputs. The evaluation indicates a gap between normative objectives and actual implementation, while IDI trends show no significant improvement in democratic quality. This study offers an outcome-based evaluation approach by integrating Dunn’s framework and the IDI, highlighting the need to reorient Banparpol from an administrative compliance model toward a performance- and impact-based policy.